2014
DOI: 10.1007/s12010-014-1132-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Fabrication of Tissue-Engineered Bone Substitutes Based on Derived Cancellous Bone Scaffold in a Spinner Flask Bioreactor System

Abstract: The in vitro dynamic fabrications of tissue-engineered bones were performed to assess the advantages of human adipose-derived stem cells (hADSCs) combined with acellular cancellous bone scaffold coming from fresh pig femur in a spinner flask compared with traditional static culture. In this study, the bio-derived cancellous bone was regarded as a biomimetic scaffold, and its surface appearance was observed under scanning electron microscopy (SEM). Moreover, its modulus of elasticity and chemical composition we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…This study demonstrated that improving the quality of culture environment by using spinner bioreactor provided a dynamic microenvironment within the interconnected pores which enhanced nutrient necessary for cells cultivation. This finding is in agreement with many previous studies showing that spinner flask could mitigate the mass transport limitation and promote cells proliferation, differentiation, and expression of osteogenic markers [ 22 , 23 ]. In addition, the cellular trend observed in ROS/HA-TCP construct was in some way consistent with normal osteoblasts’ growth sequence which consists of three principle periods.…”
Section: Discussionsupporting
confidence: 93%
“…This study demonstrated that improving the quality of culture environment by using spinner bioreactor provided a dynamic microenvironment within the interconnected pores which enhanced nutrient necessary for cells cultivation. This finding is in agreement with many previous studies showing that spinner flask could mitigate the mass transport limitation and promote cells proliferation, differentiation, and expression of osteogenic markers [ 22 , 23 ]. In addition, the cellular trend observed in ROS/HA-TCP construct was in some way consistent with normal osteoblasts’ growth sequence which consists of three principle periods.…”
Section: Discussionsupporting
confidence: 93%
“…However, the scaffold is not only a passive support but also provides cells and signals that induce the development of new bone 17 . A wide range of scaffolds that are effective in tissue-engineered bone regeneration have been designed 18 19 20 21 22 23 . However, the scaffolds used in research and clinical applications are suboptimal, and improved scaffolds for in vivo bioreactors are needed.…”
mentioning
confidence: 99%
“…Seeded into a decellularized bone-derived scaffold, adipose tissue-derived stem cells are able to adhere, migrate, grow and differentiate into osteoblastic cells expressing ALP. In these 3D hydrodynamic culture conditions, the level of differentiation was higher than in static conditions [128,129]. However, Rat BM-derived MSCs better differentiated when maintained in a perfused system, rather than in spinner flasks [130].…”
Section: Bioreactors Applied To Bone Tissue Engineeringmentioning
confidence: 86%
“…De-cellularized / de-mineralized trabecular or cortical bones can be used as biomaterials, as well. They present the advantage to recapitulate the natural ECM features, and allow, therefore, attachment, proliferation and further differentiation of adipose-derived stem cells [129]. Usually, acellular ECM can be obtained after physical, chemical or enzymatic treatments [223,224].…”
Section: Biomimeticsmentioning
confidence: 99%